Copyright (c) 1990 Association of Mizar Users
environ vocabulary RLVECT_1, VECTSP_1, ARYTM_1, FUNCSDOM, VECTSP_2, RELAT_1, MOD_1, BINOP_1, LATTICES, ALGSTR_2; notation STRUCT_0, RLVECT_1, VECTSP_1, FUNCSDOM, VECTSP_2; constructors VECTSP_2, XBOOLE_0; clusters VECTSP_1, VECTSP_2, ZFMISC_1, XBOOLE_0; theorems VECTSP_1, VECTSP_2, RLVECT_1; begin definition mode AddGroup is add-associative right_zeroed right_complementable (non empty LoopStr); end; canceled 12; theorem for K be add-associative right_zeroed right_complementable right-distributive right_unital (non empty doubleLoopStr) for a be Element of K holds a * (- 1_ K) = - a proof let K be add-associative right_zeroed right_complementable right-distributive right_unital (non empty doubleLoopStr); let x be Element of K; thus x * (- 1_ K) = x * (0.K - 1_ K) by RLVECT_1:27 .= x * 0.K - x * 1_ K by VECTSP_1:43 .= 0.K - x * 1_ K by VECTSP_1:36 .= - x * 1_ K by RLVECT_1:27 .= - x by VECTSP_1:def 13; end; theorem for K be add-associative right_zeroed right_complementable left-distributive left_unital (non empty doubleLoopStr) for a be Element of K holds (- 1_ K) * a = - a proof let K be add-associative right_zeroed right_complementable left-distributive left_unital (non empty doubleLoopStr); let x be Element of K; thus (- 1_ K) * x = (0.K - 1_ K) * x by RLVECT_1:27 .= 0.K * x - 1_ K * x by VECTSP_1:45 .= 0.K - 1_ K * x by VECTSP_1:39 .= - 1_ K * x by RLVECT_1:27 .= - x by VECTSP_1:def 19; end; reserve R for Abelian add-associative right_zeroed right_complementable associative left_unital right_unital distributive (non empty doubleLoopStr), F for non degenerated Field-like Ring, x for Scalar of F, V for add-associative right_zeroed right_complementable VectSp-like (non empty VectSpStr over F), v for Vector of V; canceled 10; theorem x*v = 0.V iff x = 0.F or v = 0.V proof x*v = 0.V implies x = 0.F or v = 0.V proof assume A1: x*v = 0.V; assume A2: x<> 0.F; (x"*x)*v = x"*(0.V) by A1,VECTSP_1:def 26 .= 0.V by VECTSP_1:59; then 0.V = (1_ F)*v by A2,VECTSP_2:43; hence thesis by VECTSP_1:def 26; end; hence thesis by VECTSP_1:59; end; theorem x<>0.F implies x"*(x*v)=v proof assume A1: x<>0.F; x"*(x*v) = (x"*x)*v by VECTSP_1:def 26 .= 1_ F *v by A1,VECTSP_2:43 .= v by VECTSP_1:def 26; hence thesis; end; reserve V for add-associative right_zeroed right_complementable RightMod-like (non empty RightModStr over R); reserve x for Scalar of R; reserve v,w for Vector of V; canceled 10; theorem Th37: v*(0.R) = 0.V & v*(-1_ R) = -v & (0.V)*x = 0.V proof v + v*(0.R) = v* (1_ R) + v*(0.R) by VECTSP_2:def 23 .= v*((1_ R) + (0.R)) by VECTSP_2:def 23 .= v*(1_ R) by RLVECT_1:10 .= v by VECTSP_2:def 23 .= v + 0.V by RLVECT_1:10; hence A1: v*(0.R) = 0.V by RLVECT_1:21; v*(-(1_ R)) + v = v*( -(1_ R)) + v* (1_ R) by VECTSP_2:def 23 .= v*((-(1_ R)) + (1_ R)) by VECTSP_2:def 23 .= 0.V by A1,RLVECT_1:16; then v*(-(1_ R)) + (v + -v) = 0.V + -v by RLVECT_1:def 6; then 0.V + -v = v*(-(1_ R)) + 0.V by RLVECT_1:16 .= v*(-(1_ R)) by RLVECT_1:10; hence v*(-1_ R) = -v by RLVECT_1:10; (0.V)*x = v*((0.R) *x) by A1,VECTSP_2:def 23 .= 0.V by A1,VECTSP_1:39; hence thesis; end; theorem Th38: -v*x = v*(-x) & w - v*x = w + v*(-x) proof -v*x = (v*x) * (-1_ R) by Th37 .= v*(x* (-1_ R)) by VECTSP_2:def 23 .= v*(-(x* 1_ R)) by VECTSP_1:40; hence -v* x = v*(-x) by VECTSP_2:def 2; hence thesis by RLVECT_1:def 11; end; theorem Th39: (-v)*x = -v*x proof (-v)*x = (v*(-1_ R))*x by Th37 .= v*((-1_ R) *x) by VECTSP_2:def 23 .= v*(-(1_ R *x)) by VECTSP_1:41 .= v*(-x) by VECTSP_2:def 2; hence thesis by Th38; end; theorem (v - w)*x = v*x - w*x proof (v - w)*x = (v + (-w))*x by RLVECT_1:def 11 .= v*x + (-w) *x by VECTSP_2:def 23 .= v*x + (-w * x) by Th39; hence thesis by RLVECT_1:def 11; end; reserve F for non degenerated Field-like Ring; reserve x for Scalar of F; reserve V for add-associative right_zeroed right_complementable RightMod-like (non empty RightModStr over F); reserve v for Vector of V; canceled; theorem v*x = 0.V iff x = 0.F or v = 0.V proof v*x = 0.V implies x = 0.F or v = 0.V proof assume A1: v*x = 0.V; assume A2: x<>(0.F); v*(x*x") = (0.V)*x" by A1,VECTSP_2:def 23 .= 0.V by Th37; then 0.V = v*(1_ F) by A2,VECTSP_2:43; hence thesis by VECTSP_2:def 23; end; hence thesis by Th37; end; theorem x<>0.F implies (v*x)*x"=v proof assume A1: x<>0.F; (v*x)*x" = v*(x*x") by VECTSP_2:def 23 .= v* 1_ F by A1,VECTSP_2:43 .= v by VECTSP_2:def 23; hence thesis; end;